La tradaptation dans l’audiovisuel : truchement transculturel ou fantaisie accessoire ? - Selma Annani (Multilinguales)
Meaning in an audiovisual text is created via a diegetic mechanism set up through a meticulous systemic interaction (multimodality) on the one hand, and an extra-diegetic contribution based on an interpretative process strongly dependent on a socio-cultural background, on the other hand. This makes the audiovisual product highly sensitive during the linguistic transfer and therefore requires special attention which cannot be limited to a rigid literality in order to bring out all the semantic reliefs. The audiovisual translator must, in the interests of accessibility, efficiency and functionality, go beyond the translation itself and use adaptation as a strategy for linguistic and extra linguistic (situational, conceptual, contextual, etc.) adjustment, with the sole aim of avoiding communicational disturbances that can strongly remind the translation. All this without getting carried away by his creative impulse and thus distorting the original work. In short, the audiovisual translator must master the exercise of loyalty and the art of illusion.